Odpowiedź :
a) -7(x + 2) + 4 = -3x
-7x -14 + 4 = -3x
-10=10x
x=-1
b) 1 - 2x+5/3 = 4
-3+5/3 =2x
-2+2/3 =2x
x=-1 + 1/3
x=- 2/3
c) -4(½x - 2) - 4 = 2(-x+2)
-2x + 8 -4 = -2x +4
4=4
d) 2x(x-1) = 2(x-1)(x+3)
2x² -2x = 2( x² +3x-x-3)
2x² -2x = 2x² + 6x-2x-6
2x² - 2x= 2x²+4x-6
-2x=4x-6
6=2x
x=3
a)-7(x + 2) + 4 = -3x
-7x -14 +4 = -3x
-7x -10 =-3x
-7x+ 3x = 10
-4x = 10
x = 2,5
b) 1 - 2x+5/3 = 4
6- 2x/3 = 4
2-2x= 4
-2x= 4-2
x=-1
c) -4(½x - 2) - 4 = 2(-x+2)
-4*½x + 6 - 4 = 2* -x +4
-4*½x +2 = 2* -x +4
-2½x = 6-x
½x + x = 6 +2
½x = 8
x= 16
-7x -14 +4 = -3x
-7x -10 =-3x
-7x+ 3x = 10
-4x = 10
x = 2,5
b) 1 - 2x+5/3 = 4
6- 2x/3 = 4
2-2x= 4
-2x= 4-2
x=-1
c) -4(½x - 2) - 4 = 2(-x+2)
-4*½x + 6 - 4 = 2* -x +4
-4*½x +2 = 2* -x +4
-2½x = 6-x
½x + x = 6 +2
½x = 8
x= 16
1
a) -7(x+2)+4=-3x
-7x-14+4=-3x
-7x+3x=10
4x=10
x=2,5
b) 1-2x+5/3=4 /razy 3 obie strony
1-2x+5=12
-2x=6
x=-3
c) -4(1/2x-2)-4=2(-x+2)
-2x+8-4=-2x+4
0=0
d) 2x(x-1)=2(x-1)(x+3)
2x²-2x=2(x²+3x-x-3)
2x² -2x= 2x² +4x-6
2x²-2x²-2x-4x=-6
-6x=-6
x=1
2
a)x/2=5/6
3x=5
x=5/3
b) x/2=x+1/4
2x=4x+1
2x-4x=1
-2x=1
x=-1/2
c) 2(x-1)/3=x+2/5
10x-10=3x+6
7x=16
x=16/7
a) -7(x+2)+4=-3x
-7x-14+4=-3x
-7x+3x=10
4x=10
x=2,5
b) 1-2x+5/3=4 /razy 3 obie strony
1-2x+5=12
-2x=6
x=-3
c) -4(1/2x-2)-4=2(-x+2)
-2x+8-4=-2x+4
0=0
d) 2x(x-1)=2(x-1)(x+3)
2x²-2x=2(x²+3x-x-3)
2x² -2x= 2x² +4x-6
2x²-2x²-2x-4x=-6
-6x=-6
x=1
2
a)x/2=5/6
3x=5
x=5/3
b) x/2=x+1/4
2x=4x+1
2x-4x=1
-2x=1
x=-1/2
c) 2(x-1)/3=x+2/5
10x-10=3x+6
7x=16
x=16/7